A method for preparing piezoelectric ceramics by low temperature sintering

By combining sol-hydrothermal method and solid-phase sintering method, the sintering temperature of PZT-based piezoelectric ceramics is reduced, and the lead volatility caused by high sintering temperature is solved, and excellent piezoelectric performance and environmentally friendly process are achieved.

CN119306495BActive Publication Date: 2025-03-07HUNAN MEICHENG NEW MATERIALS TECHNOLOGY CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411865323.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-18
Publication Date
2025-03-07
Estimated Expiration
2044-12-18

Smart Images

  • Figure CN119306495B_ABST
    Figure CN119306495B_ABST
Patent Text Reader

Abstract

The present invention relates to the field of piezoelectric ceramic materials, and in particular to a method for preparing piezoelectric ceramics by low temperature sintering, wherein a first mixed powder is prepared by a sol-hydrothermal method, and the first mixed powder is mixed with MCO 3 , Ga 2 O 3 , Nb 2 O 5 , CuO are mixed once and ball-milled, then dried to obtain a second mixed powder, the second mixed powder is pre-calcined, ball-milled for a second time and dried, and then granulated, sifted and pressed to obtain a green body, the green body is first heated to 550-650°C for insulation and debinding for 1-3 h, and then heated to 1000-1100°C for sintering for 1-3 h to obtain the piezoelectric ceramic, wherein M is an alkaline earth metal. The piezoelectric ceramic prepared by the method of the present invention still has excellent piezoelectric properties when sintered at low temperature, and has industrial application value and market prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of piezoelectric ceramic materials, in particular to a method for preparing piezoelectric ceramics by low-temperature sintering. Background Art

[0002] Lead zirconate titanate (PZT)-based piezoelectric ceramics have been widely used in the preparation of sensors, receivers, filters, ultrasonic transducers, etc. due to their excellent electrical properties and low production costs. However, the sintering temperature of PZT-based ceramics is usually greater than 1200°C, and there will be serious lead volatilization during the sintering process, which will pollute the environment and cause harm to human health. If the sintering temperature of PZT-based ceramics can be reduced to about 1000°C, it will greatly reduce the harm caused by lead volatilization. Summary of the invention

[0003] Purpose of the invention: In view of the above technical problems, the present invention proposes a method for preparing piezoelectric ceramics by low-temperature sintering.

[0004] The technical solutions adopted are as follows:

[0005] A method for preparing piezoelectric ceramics by low temperature sintering, as follows:

[0006] Lead acetate and lithium acetate are dissolved in acetic acid solution to obtain solution A and solution B respectively, zirconium n-propoxide and aluminum isopropoxide are dissolved in anhydrous ethanol to obtain solution C and solution D respectively, solution B, solution C, solution D and tetrabutyl titanate are added to solution A under constant stirring, diethanolamine and deionized water are added, the obtained mixed system is heated in a water bath to 40-60° C. and stirred for reaction for 1-5 hours to obtain a sol, an alkali solution is added to the sol and mixed, the temperature is raised to 150-200° C. in a sealed state for solvent thermal reaction for 12-24 hours, the product is collected, washed and dried to obtain a first mixed powder;

[0007] The first mixed powder is mixed with MCO3, Ga2O3, Nb2O5, and CuO, ball-milled once, and then dried to obtain a second mixed powder. The second mixed powder is pre-sintered, ball-milled twice, and dried. The green body is then granulated, sieved, and pressed to obtain the green body. The green body is first heated to 550-650°C for insulation and debinding for 1-3 hours, and then heated to 1000-1100°C for sintering for 1-3 hours to obtain the piezoelectric ceramic, wherein M is an alkaline earth metal.

[0008] Furthermore, the chemical structure formula of the piezoelectric ceramic is as follows:

[0009] Pb 1-α (Al 0.5 Li 0.5 ) α (Zr 0.5 Ti 0.5 )O3-xwt%M(Ga0.5 Nb 0.5 )O3-ywt%CuO

[0010] Among them, 0<α≤0.1, 1≤x≤5, 0.1≤y≤1.

[0011] Further, M is Sr.

[0012] Furthermore, 0.04≤α≤0.06.

[0013] Furthermore, α=0.05.

[0014] Furthermore, 2≤x≤4, 0.3≤y≤0.5.

[0015] Furthermore, x=2.5, y=0.4.

[0016] Furthermore, the alkali solution is a sodium hydroxide solution and / or a potassium hydroxide solution, the concentration of the sodium hydroxide solution is 1-4 mol / L, and the concentration of the potassium hydroxide solution is 1-4 mol / L.

[0017] Furthermore, the pre-firing temperature is 700-800° C., and the pre-firing time is 1-3 hours.

[0018] Furthermore, the heating rate in the first stage of heating is 1-5°C / min, and the heating rate in the second stage of heating is 10-30°C / min.

[0019] Beneficial effects of the present invention:

[0020] The present invention provides a method for preparing piezoelectric ceramics by low-temperature sintering, which combines a sol-hydrothermal method and a solid-phase sintering method. By optimizing process conditions, piezoelectric ceramics with excellent piezoelectric properties are synthesized. The sol-hydrothermal method can successfully synthesize single-phase, pure, cubic A-site doped PZT ceramic powders with an average particle size at the nanometer level, which not only realizes uniform mixing of raw materials, but also makes each component easy to control, effectively avoiding defects that may be caused by component changes, and creating conditions for subsequent solid-phase sintering.

[0021] At present, the research on PZT ceramics is mostly about single atom substitution of Pb on the A position. 2+ Or Zr in B position 4+ 、Ti 4+ ions, rarely seen complex ions for Pb at the A position 2+ To replace, in this application, (Al 0.5 Li 0.5 ) 2+ The complex ion pairs Pb at the A site 2+Equivalent doping substitution will cause lattice distortion in the crystal. This moderate lattice distortion can give full play to the piezoelectricity of the material and improve the piezoelectric performance of piezoelectric ceramics.

[0022] M(Ga 0.5 Nb 0.5 )O3 is an ABO3 type perovskite structure, which can form a multinary solid solution with PZT having a quasi-isotropic phase boundary. Near the quasi-isotropic phase boundary component, under the action of an external electric field or stress, spontaneous polarization becomes easier to change direction, and the piezoelectric performance will be greatly improved. The addition of CuO does not change the main crystal phase structure of the piezoelectric ceramic, but it can effectively reduce the sintering temperature and generate a liquid phase to fill the internal pores of the ceramic during sintering, thereby improving the density and electrical properties of the material. The piezoelectric ceramic prepared by the method of the present invention still has excellent piezoelectric properties when sintered at low temperature (about 1000°C), and has industrial application value and market prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 This is the SEM image of the piezoelectric ceramic prepared in Example 1. DETAILED DESCRIPTION

[0024] If the specific conditions are not specified in the examples, the experiments were carried out under conventional conditions or the conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments is not specified, they are all conventional products that can be purchased commercially. The techniques not mentioned in the present invention are all referenced to the prior art. Unless otherwise specified, the following examples and comparative examples are parallel experiments, using the same processing steps and parameters.

[0025] Embodiment 1:

[0026] This embodiment provides a method for preparing piezoelectric ceramics by low temperature sintering:

[0027] The general chemical structure formula of piezoelectric ceramics is shown below:

[0028] Pb 0.95 (Al 0.5 Li 0.5 ) 0.05 (Zr 0.5 Ti 0.5 )O3-2.5wt%Sr(Ga 0.5 Nb 0.5 )O3-0.4wt%CuO

[0029] 0.95 mol of lead acetate and 0.025 mol of lithium acetate were dissolved in 1 mol / L acetic acid solution at a solid-liquid mass ratio of 1:10 to obtain solutions A and B, 0.5 mol of zirconium n-propoxide and 0.025 mol of aluminum isopropoxide were dissolved in anhydrous ethanol at a solid-liquid mass ratio of 1:10 to obtain solutions C and D, solution B, solution C, solution D and 0.5 mol of tetrabutyl titanate were added to solution A under constant stirring, 50 ml of diethanolamine and 100 ml of deionized water were added, the obtained mixed system was heated to 60° C. in a water bath and stirred for reaction for 2 h to obtain a sol, a 2 mol / L potassium hydroxide solution was slowly added to the sol and mixed to adjust the pH value of the system to 10, the reaction solution was transferred to a high-pressure reactor, the temperature was raised to 180° C. for solvent thermal reaction for 20 h in a sealed state, the product was collected, and it was repeatedly washed with deionized water and ethanol until neutral and then dried to obtain a first mixed powder;

[0030] According to the ratio in the chemical structure formula, the first mixed powder and SrCO3, Ga2O3, Nb2O5, and CuO are placed in a ball mill, and a sufficient amount of ethanol is added as a medium. The ball mill is then placed in a planetary ball mill for 12 hours and dried to obtain a second mixed powder. The second mixed powder is placed in a crucible and compacted. The crucible is heated to 780°C at a rate of 1°C / min and pre-fired for 2 hours. After naturally cooling to room temperature, it is taken out and placed in the ball mill again. Add enough ethanol as the medium, then place the ball mill in a planetary ball mill for secondary ball milling for 12 hours and then dry, then use 8wt% PVA aqueous solution as a binder to make granules, the obtained granules are sieved with an 80-mesh sieve and added to the mold, and pressed into a green body with a pressure of 100MPa. The green body is first heated to 600℃ at a heating rate of 2℃ / min in one stage, kept warm for 2 hours to debind, and then heated to 1050℃ at a heating rate of 10℃ / min in two stages, kept warm for sintering for 2 hours.

[0031] Embodiment 2:

[0032] This embodiment provides a method for preparing piezoelectric ceramics by low temperature sintering:

[0033] The general chemical structure of piezoelectric ceramics is shown below:

[0034] Pb 0.95 (Al 0.5 Li 0.5 ) 0.05 (Zr 0.5 Ti 0.5 )O3-2.5wt%Ca(Ga 0.5 Nb 0.5 )O3-0.4wt%CuO

[0035] 0.95 mol of lead acetate and 0.025 mol of lithium acetate were dissolved in 1 mol / L acetic acid solution at a solid-liquid mass ratio of 1:10 to obtain solutions A and B, 0.5 mol of zirconium n-propoxide and 0.025 mol of aluminum isopropoxide were dissolved in anhydrous ethanol at a solid-liquid mass ratio of 1:10 to obtain solutions C and D, solution B, solution C, solution D and 0.5 mol of tetrabutyl titanate were added to solution A under constant stirring, 50 ml of diethanolamine and 100 ml of deionized water were added, the obtained mixed system was heated to 60° C. in a water bath and stirred for reaction for 2 h to obtain a sol, a 2 mol / L potassium hydroxide solution was slowly added to the sol and mixed to adjust the pH value of the system to 10, the reaction solution was transferred to a high-pressure reactor, the temperature was raised to 180° C. for solvent thermal reaction for 20 h in a sealed state, the product was collected, and it was repeatedly washed with deionized water and ethanol until neutral and then dried to obtain a first mixed powder;

[0036] According to the ratio in the chemical structure formula, the first mixed powder and CaCO3, Ga2O3, Nb2O5, and CuO are placed in a ball mill, and a sufficient amount of ethanol is added as a medium. The ball mill is then placed in a planetary ball mill for 12 hours and dried to obtain a second mixed powder. The second mixed powder is placed in a crucible and compacted. The crucible is heated to 780°C at a rate of 1°C / min and pre-fired for 2 hours. After naturally cooling to room temperature, it is taken out and placed in the ball mill again. Add enough ethanol as the medium, then place the ball mill in a planetary ball mill for secondary ball milling for 12 hours and then dry, then use 8wt% PVA aqueous solution as a binder to make granules, the obtained granules are sieved with an 80-mesh sieve and added to the mold, and pressed into a green body with a pressure of 100MPa. The green body is first heated to 600℃ at a heating rate of 2℃ / min in one stage, kept warm for 2 hours to debind, and then heated to 1050℃ at a heating rate of 10℃ / min in two stages, kept warm for sintering for 2 hours.

[0037] Embodiment 3:

[0038] This embodiment provides a method for preparing piezoelectric ceramics by low temperature sintering:

[0039] The general chemical structure of piezoelectric ceramics is shown below:

[0040] Pb 0.95 (Al 0.5 Li 0.5 ) 0.05 (Zr 0.5 Ti 0.5 )O3-2.5wt%Ba(Ga 0.5 Nb 0.5 )O3-0.4wt%CuO

[0041] 0.95 mol of lead acetate and 0.025 mol of lithium acetate were dissolved in 1 mol / L acetic acid solution at a solid-liquid mass ratio of 1:10 to obtain solutions A and B, 0.5 mol of zirconium n-propoxide and 0.025 mol of aluminum isopropoxide were dissolved in anhydrous ethanol at a solid-liquid mass ratio of 1:10 to obtain solutions C and D, solution B, solution C, solution D and 0.5 mol of tetrabutyl titanate were added to solution A under constant stirring, 50 ml of diethanolamine and 100 ml of deionized water were added, the obtained mixed system was heated to 60° C. in a water bath and stirred for reaction for 2 h to obtain a sol, a 2 mol / L potassium hydroxide solution was slowly added to the sol and mixed to adjust the pH value of the system to 10, the reaction solution was transferred to a high-pressure reactor, the temperature was raised to 180° C. for solvent thermal reaction for 20 h in a sealed state, the product was collected, and it was repeatedly washed with deionized water and ethanol until neutral and then dried to obtain a first mixed powder;

[0042] According to the ratio in the chemical structure formula, the first mixed powder and BaCO3, Ga2O3, Nb2O5, and CuO are placed in a ball mill, and a sufficient amount of ethanol is added as a medium. The ball mill is then placed in a planetary ball mill for 12 hours and dried to obtain a second mixed powder. The second mixed powder is placed in a crucible and compacted. The crucible is heated to 780°C at a rate of 1°C / min and pre-fired for 2 hours. After naturally cooling to room temperature, it is taken out and placed in the ball mill again. Add enough ethanol as the medium, then place the ball mill in a planetary ball mill for secondary ball milling for 12 hours and then dry, then use 8wt% PVA aqueous solution as a binder to make granules, the obtained granules are sieved with an 80-mesh sieve and added to the mold, and pressed into a green body with a pressure of 100MPa. The green body is first heated to 600℃ at a heating rate of 2℃ / min in one stage, kept warm for 2 hours to debind, and then heated to 1050℃ at a heating rate of 10℃ / min in two stages, kept warm for sintering for 2 hours.

[0043] Embodiment 4:

[0044] This embodiment provides a method for preparing piezoelectric ceramics by low temperature sintering:

[0045] The general chemical structure of piezoelectric ceramics is shown below:

[0046] Pb 0.95 (Al 0.5 Li 0.5 ) 0.05 (Zr 0.5 Ti 0.5 )O3-2.5wt%Sr(Ga 0.5 Nb 0.5 )O3-0.4wt%CuO

[0047] 0.95 mol of lead acetate and 0.025 mol of lithium acetate were dissolved in 1 mol / L acetic acid solution at a solid-liquid mass ratio of 1:10 to obtain solutions A and B, 0.5 mol of zirconium n-propoxide and 0.025 mol of aluminum isopropoxide were dissolved in anhydrous ethanol at a solid-liquid mass ratio of 1:10 to obtain solutions C and D, solution B, solution C, solution D and 0.5 mol of tetrabutyl titanate were added to solution A under constant stirring, 50 ml of diethanolamine and 100 ml of deionized water were added, the obtained mixed system was heated to 60° C. in a water bath and stirred for reaction for 2 h to obtain a sol, a 2 mol / L potassium hydroxide solution was slowly added to the sol and mixed to adjust the pH value of the system to 10, the reaction solution was transferred to a high-pressure reactor, the temperature was raised to 180° C. for solvent thermal reaction for 20 h in a sealed state, the product was collected, and it was repeatedly washed with deionized water and ethanol until neutral and then dried to obtain a first mixed powder;

[0048] According to the ratio in the chemical structure formula, the first mixed powder and SrCO3, Ga2O3, Nb2O5, and CuO are placed in a ball mill, and a sufficient amount of ethanol is added as a medium. The ball mill is then placed in a planetary ball mill for 12 hours and dried to obtain a second mixed powder. The second mixed powder is placed in a crucible and compacted. The crucible is heated to 780°C at a rate of 1°C / min and pre-fired for 2 hours. After naturally cooling to room temperature, it is taken out and placed in the ball mill again. Add enough ethanol as the medium, then place the ball mill in a planetary ball mill for secondary ball milling for 12 hours and then dry, then use 8wt% PVA aqueous solution as a binder to make granules, the obtained granules are sieved with an 80-mesh sieve and added to the mold, and pressed into a green body with a pressure of 100MPa. The green body is first heated to 600℃ at a heating rate of 2℃ / min in one stage, kept warm for 2 hours to debind, and then heated to 1000℃ at a heating rate of 10℃ / min in two stages, kept warm for sintering for 2 hours.

[0049] Embodiment 5:

[0050] This embodiment provides a method for preparing piezoelectric ceramics by low temperature sintering:

[0051] The general chemical structure formula of piezoelectric ceramics is shown below:

[0052] Pb 0.95 (Al 0.5 Li 0.5 ) 0.05 (Zr 0.5 Ti 0.5 )O3-2.5wt%Sr(Ga 0.5 Nb 0.5 )O3-0.4wt%CuO

[0053] 0.95 mol of lead acetate and 0.025 mol of lithium acetate were dissolved in 1 mol / L acetic acid solution at a solid-liquid mass ratio of 1:10 to obtain solutions A and B, 0.5 mol of zirconium n-propoxide and 0.025 mol of aluminum isopropoxide were dissolved in anhydrous ethanol at a solid-liquid mass ratio of 1:10 to obtain solutions C and D, solution B, solution C, solution D and 0.5 mol of tetrabutyl titanate were added to solution A under constant stirring, 50 ml of diethanolamine and 100 ml of deionized water were added, the obtained mixed system was heated to 60° C. in a water bath and stirred for reaction for 2 h to obtain a sol, a 2 mol / L potassium hydroxide solution was slowly added to the sol and mixed to adjust the pH value of the system to 10, the reaction solution was transferred to a high-pressure reactor, the temperature was raised to 180° C. for solvent thermal reaction for 20 h in a sealed state, the product was collected, and it was repeatedly washed with deionized water and ethanol until neutral and then dried to obtain a first mixed powder;

[0054] According to the ratio in the chemical structure formula, the first mixed powder and SrCO3, Ga2O3, Nb2O5, and CuO are placed in a ball mill, and a sufficient amount of ethanol is added as a medium. The ball mill is then placed in a planetary ball mill for 12 hours and dried to obtain a second mixed powder. The second mixed powder is placed in a crucible and compacted. The crucible is heated to 780°C at a rate of 1°C / min and pre-fired for 2 hours. After naturally cooling to room temperature, it is taken out and placed in the ball mill again. Add enough ethanol as the medium, then place the ball mill in a planetary ball mill for secondary ball milling for 12 hours and then dry, then use 8wt% PVA aqueous solution as a binder to make granules, the obtained granules are sieved with an 80-mesh sieve and added to the mold, and pressed into a green body with a pressure of 100MPa. The green body is first heated to 600℃ at a heating rate of 2℃ / min in one stage, kept warm for 2h to debind, and then heated to 1100℃ at a heating rate of 10℃ / min in two stages, kept warm for sintering for 2h.

[0055] Comparative Example 1:

[0056] It is basically the same as Example 1, except that Pb 0.95 (Al 0.5 Li 0.5 ) 0.05 (Zr 0.5 Ti 0.5 )O3 with Pb(Zr 0.5 Ti 0.5 )O3 instead;

[0057] This comparative example provides a method for preparing piezoelectric ceramics by low temperature sintering:

[0058] The general chemical structure formula of piezoelectric ceramics is shown below:

[0059] Pb(Zr 0.5 Ti 0.5)O3-2.5wt%Sr(Ga 0.5 Nb 0.5 )O3-0.4wt%CuO

[0060] 1 mol of lead acetate is dissolved in a 1 mol / L acetic acid solution at a solid-liquid mass ratio of 1:10 to obtain solution A, 0.5 mol of zirconium n-propoxide is dissolved in anhydrous ethanol at a solid-liquid mass ratio of 1:10 to obtain solution B, solution B and 0.5 mol of tetrabutyl titanate are added to solution A under continuous stirring, 50 ml of diethanolamine and 100 ml of deionized water are added, the obtained mixed system is heated to 60°C in a water bath and stirred for reaction for 2 hours to obtain a sol, a 2 mol / L potassium hydroxide solution is slowly added to the sol and mixed to adjust the pH value of the system to 10, the reaction solution is transferred to a high-pressure reactor, the temperature is raised to 180°C for solvent thermal reaction for 20 hours, the product is collected, and the product is repeatedly washed with deionized water and ethanol until neutral and then dried to obtain a first mixed powder;

[0061] According to the ratio in the chemical structure formula, the first mixed powder and SrCO3, Ga2O3, Nb2O5, and CuO are placed in a ball mill, and a sufficient amount of ethanol is added as a medium. The ball mill is then placed in a planetary ball mill for 12 hours and dried to obtain a second mixed powder. The second mixed powder is placed in a crucible and compacted. The crucible is heated to 780°C at a rate of 1°C / min and pre-fired for 2 hours. After naturally cooling to room temperature, it is taken out and placed in the ball mill again. Add enough ethanol as the medium, then place the ball mill in a planetary ball mill for secondary ball milling for 12 hours and then dry, then use 8wt% PVA aqueous solution as a binder to make granules, the obtained granules are sieved with an 80-mesh sieve and added to the mold, and pressed into a green body with a pressure of 100MPa. The green body is first heated to 600℃ at a heating rate of 2℃ / min in one stage, kept warm for 2 hours to debind, and then heated to 1050℃ at a heating rate of 10℃ / min in two stages, kept warm for sintering for 2 hours.

[0062] Comparative Example 2:

[0063] The same as Example 1, except that the composition of the piezoelectric ceramic does not contain Sr (Ga 0.5 Nb 0.5 )O3, that is, SrCO3, Ga2O3 and Nb2O5 are not added during the preparation.

[0064] Comparative Example 3:

[0065] The method is basically the same as Example 1, except that the piezoelectric ceramic does not contain CuO, that is, CuO is not added during preparation.

[0066] Comparative Example 4:

[0067] The method is basically the same as Example 1, except that the piezoelectric ceramic is prepared by a conventional solid phase method;

[0068] This comparative example provides a method for preparing piezoelectric ceramics by low temperature sintering:

[0069] The general chemical structure formula of piezoelectric ceramics is shown below:

[0070] Pb 0.95 (Al 0.5 Li 0.5 ) 0.05 (Zr 0.5 Ti 0.5 )O3-2.5wt%Sr(Ga 0.5 Nb 0.5 )O3-0.4wt%CuO

[0071] According to the ratio in the chemical structure formula, PbO, Al2O3, Li2CO3, ZrO2, TiO2, SrCO3, Ga2O3, Nb2O5, and CuO are placed in a ball mill, and a sufficient amount of ethanol is added as a medium. The ball mill is then placed in a planetary ball mill and ball milled for 12 hours, and then dried to obtain a mixed powder. The mixed powder is placed in a crucible and compacted, and the crucible is heated to 780°C at a rate of 1°C / min and pre-fired for 2 hours. After naturally cooling to room temperature, it is taken out and placed again. After entering the ball mill, add a sufficient amount of ethanol as a medium, then place the ball mill in a planetary ball mill for secondary ball milling for 12 hours and then dry, and then granulate with 8wt% PVA aqueous solution as a binder. The obtained granules are sieved with an 80-mesh sieve and added to the mold, and pressed into a green body with a pressure of 100MPa. The green body is first heated to 600℃ at a heating rate of 2℃ / min in one stage and kept warm for 2 hours to debind, and then heated to 1050℃ at a heating rate of 10℃ / min in two stages and kept warm for sintering for 2 hours.

[0072] Performance Testing:

[0073] The surfaces of the piezoelectric ceramics prepared in Examples 1-5 and Comparative Examples 1-4 were polished, coated with silver paste on both sides, kept at 750°C for 10 min, and finally polarized at a DC voltage of 4 kV / mm for 20 min in silicone oil at 120°C and placed for 24 h to test their electrical properties as samples.

[0074] The room temperature piezoelectric constant of the sample was measured using a ZJ-3AN quasi-static piezoelectric constant tester. d 33 ;

[0075] The electromechanical coupling coefficient kp, mechanical quality factor Qm and dielectric loss tanδ (25°C, 1V, 1kHz) of the samples were measured and analyzed using a precision impedance analyzer (Agilent HP4294A).

[0076] The test results are shown in Table 1 below:

[0077] ;

[0078] It can be seen from Table 1 above that the piezoelectric ceramics prepared by the method of the present invention have excellent piezoelectric properties;

[0079] It can be seen from the comparison of Examples 1-3 that the introduction of different alkaline earth metal elements will affect the piezoelectric properties of the prepared piezoelectric ceramics. When M=Sr, the piezoelectric properties of the piezoelectric ceramics are optimal.

[0080] By comparing Example 1 with Examples 4-5, it can be seen that the piezoelectric properties of piezoelectric ceramics prepared at different sintering temperatures are different. When the sintering temperature is 1050°C, the piezoelectric properties of the piezoelectric ceramics are optimal.

[0081] By comparing Example 1 with Comparative Examples 1-3, it can be seen that (Al 0.5 Li 0.5 ) 2+ Composite ion doping, Sr(Ga 0.5 Nb 0.5 ) The introduction of O3 and CuO plays a positive role in improving the piezoelectric properties of the piezoelectric ceramics in this application;

[0082] By comparing Example 1 with Comparative Example 4, it can be seen that the piezoelectric ceramics prepared by the method of the present invention have better piezoelectric properties than those prepared by the traditional solid phase method.

[0083] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for preparing piezoelectric ceramics by low temperature sintering, characterized in that: The details are as follows: Lead acetate and lithium acetate are dissolved in acetic acid solution to obtain solution A and solution B respectively, zirconium n-propoxide and aluminum isopropoxide are dissolved in anhydrous ethanol to obtain solution C and solution D respectively, solution B, solution C, solution D and tetrabutyl titanate are added to solution A under constant stirring, diethanolamine and deionized water are added, the obtained mixed system is heated in a water bath to 40-60° C. and stirred for reaction for 1-5 hours to obtain a sol, an alkali solution is added to the sol and mixed, the temperature is raised to 150-200° C. in a sealed state for solvent thermal reaction for 12-24 hours, the product is collected, washed and dried to obtain a first mixed powder; The first mixed powder is mixed with MCO3, Ga2O3, Nb2O5, and CuO, ball-milled once, and then dried to obtain a second mixed powder, the second mixed powder is pre-sintered, ball-milled twice, and dried, and then granulated, sieved, and pressed to obtain a green body, the green body is first heated to 550-650°C for heat preservation and debinding for 1-3h, and then heated to 1000-1100°C for sintering for 1-3h to obtain the piezoelectric ceramic, wherein M is an alkaline earth metal; The general chemical structure formula of the piezoelectric ceramic is as follows: <h2 style=";text-align:left;direction:ltr">Pb<h2 style=";text-align:left;direction:ltr"> 1-α <h2 style=";text-align:left;direction:ltr"> (Al<h2 style=";text-align:left;direction:ltr"> 0.5 <h2 style=";text-align:left;direction:ltr"> Li<h2 style=";text-align:left;direction:ltr"> 0.5 <h2 style=";text-align:left;direction:ltr"> )<h2 style=";text-align:left;direction:ltr"> α <h2 style=";text-align:left;direction:ltr"> (Zr<h2 style=";text-align:left;direction:ltr"> 0.5 <h2 style=";text-align:left;direction:ltr"> Ti<h2 style=";text-align:left;direction:ltr"> 0.5 <h2 style=";text-align:left;direction:ltr"> )O3-xwt%Sr(Ga<h2 style=";text-align:left;direction:ltr"> 0.5 <h2 style=";text-align:left;direction:ltr"> Nb<h2 style=";text-align:left;direction:ltr"> 0.5 <h2 style=";text-align:left;direction:ltr"> )O3-ywt%CuO Among them, 0.04≤α≤0.06, 2≤x≤4, 0.3≤y≤0.

5.

2. The method for preparing piezoelectric ceramics by low temperature sintering according to claim 1, characterized in that: α=0.05。 3. The method for preparing piezoelectric ceramics by low temperature sintering according to claim 1, characterized in that: x=2.5,y=0.

4.

4. The method for preparing piezoelectric ceramics by low temperature sintering according to claim 1, characterized in that: The alkali solution is a sodium hydroxide solution and / or a potassium hydroxide solution, the concentration of the sodium hydroxide solution is 1-4 mol / L, and the concentration of the potassium hydroxide solution is 1-4 mol / L.

5. The method for preparing piezoelectric ceramics by low temperature sintering according to claim 1, characterized in that: The pre-firing temperature is 700-800°C and the pre-firing time is 1-3h.

6. The method for preparing piezoelectric ceramics by low temperature sintering according to claim 1, characterized in that: The heating rate during the first stage of heating is 1-5°C / min, and the heating rate during the second stage of heating is 10-30°C / min.

Citation Information

Patent Citations

  • Sol-gel method of making ceramics

    EP0338799A2